KEBUDAYAAN SEBAGAI SUATU SINTESA EKONOMI ISLAM (Studi Antropologi Ekonomi Islam Pada Keraton Cirebon) - Yanuar Isyanto; Yanuar Isyanto; Karlina Karlina; Karlina Karlina (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2023)
Humans are actually social beings who can always be relied on mutually between individuals and individuals, individuals with groups or groups. From this interaction humans create a habit or often called a "tradition" which is implemented based on a system of noble norms and values from generation to generation. The tradition of integrating a value system with the beliefs held through cultural acculturation and also correlating it to dynamic forms within the scope of other social sciences, for example, can have a systemic impact on society. Tradition is like a normative rule encapsulated by religious values, similar to the tradition of the Cirebon people at the Muludan market which can attract the attention of tourists. Not only preserving culture, but the muludan market is a potential in developing a creative economy which is seen from the point of view of sharia tourism as part of the value system of culture.Keywords: Culture, Creative Economy, Syari'ah Tourism